2013
DOI: 10.1002/anie.201304492
|View full text |Cite
|
Sign up to set email alerts
|

CH Alkenylation of Azoles with Enols and Esters by Nickel Catalysis

Abstract: Rather u(Ni)que: Two new C-H alkenylation reactions, that is C-H/C-O alkenylation and decarbonylative C-H alkenylation, of azoles are uniquely catalyzed by Ni/dcype. These azole alkenylation reactions are successfully applied to the convergent formal synthesis of siphonazole B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(59 citation statements)
references
References 82 publications
2
51
0
1
Order By: Relevance
“…During their studies into C-H/C-O couplings, Itami and coworkers found that, under identical reaction conditions, when an aryl or alkenyl ester is used, rather than pivaloyl esters, a decarbonylative coupling was observed (Chart 8) [81,82]. The authors propose this reaction proceeds via oxidative addition into the C (acyl) -O bond, followed by decarbonylation and C-H activation to generate the bisarylated nickel(II) species.…”
Section: Nickel Catalysismentioning
confidence: 91%
“…During their studies into C-H/C-O couplings, Itami and coworkers found that, under identical reaction conditions, when an aryl or alkenyl ester is used, rather than pivaloyl esters, a decarbonylative coupling was observed (Chart 8) [81,82]. The authors propose this reaction proceeds via oxidative addition into the C (acyl) -O bond, followed by decarbonylation and C-H activation to generate the bisarylated nickel(II) species.…”
Section: Nickel Catalysismentioning
confidence: 91%
“…For example, we demonstrated the coupling of benzoxazole (80) with styryl pivalate (102), carbamate (102¤), and phenyl cinnamate (103) as alkenylating agents (Scheme 29). 40 Thus, 80 was coupled with 102 (1.5 equiv) in the presence of Ni(cod) 2 (10 mol %), dcype (20 mol %), and K 3 PO 4 (2.0 equiv) in 1,4-dioxane at 130°C to produce 104 in 47% yield (CH/CO alkenylation). When styryl carbamate (102¤) was used instead of pivalate 102, 104 was obtained in 77% yield.…”
Section: Ni-catalyzed Ch Coupling Of Azoles With Aryl Electrophilesmentioning
confidence: 99%
“…Thiazole (42) was coupled with iodobenzene under Pd(OAc) 2 /CuI catalysis 22 to give 2-phenylthiazole (40) in 72% yield. Thereafter, palladium-catalyzed C4-selective CH arylation of 40 with p-tolylboronic acid (14b) was conducted under the influence of Pd(OAc) 2 /phen/ TEMPO/LiBF 4 to furnish the corresponding 2,4-diarylthiazole 41b in 75% yield with >95% regioselectivity.…”
mentioning
confidence: 99%
“…Meanwhile, in 2013, Yamaguchi, Itami, and coworkers reported a C-H alkenylation of 1,3-azoles with enol derivatives (C-H/C-O type alkenylation) or alkenyl esters (decarbonylative C-H alkenylation) as electrophiles and applied this strategy to the formal synthesis of siphonazole B (Scheme 16.29b) [63]. Oxazole 137 was coupled with enol derivative 144 under their nickel catalytic system using the dcype ligand to form alkenyl oxazole 145 in 72% yield by C-H alkenylation at the C2 position of oxazoles.…”
Section: Annuloline and Siphonazole B (C-h Alkenylation Of Oxazoles Amentioning
confidence: 99%